THE ROLE OF PEER GROUP DISCUSSION ACTIVITY TOWARD STUDENTS’ SPEAKING ANXIETY - Sasi Viviani (Journal of English Education Program (JEEP), 2020)
This paper reports on the role of peer group discussion activity towards students' speaking anxiety. This research aimed to discover find out factors affecting students’ speaking anxiety, the students’ ways to overcome their speaking anxiety, and the students’ perceptions of the role of peer group discussion activity toward students’ speaking anxiety. This research employed qualitative design in which a case study and the data were collected through questionnaires and interviews. The participant of this research was the 31 junior students of English Department Galuh University. The researcher used a close-ended questionnaire and it consists of ten statements. The data from the questionnaire analyzed by using close items on the questionnaire and the percentage computation, while the researcher used a semi-structured interview to obtain the data of the research. Furthermore, the researcher conducted a telephone interview and the data from the interview was analyzed by displaying data interpretation from the interviewees. The researcher found that students have two factors that influence their speaking anxiety, namely linguistic factors, and non-linguistic factors. Furthermore, students have two strategies to overcome their speaking anxiety namely preparation and getting help from their friends. Then, students perceive that peer group discussion activity was very helpful to overcome their speaking anxiety and improve their speaking skills because students can be more confident and comfortable talking about with their friends. They can help each other to share opinions, make conversations, and motivate them to be more confident. Students also perceive that peer group discussions can help them to improve their speaking skills because they can talk more confidently and they can help one another, correct when making mistakes, and share information about what is not understood.Keywords: peer group, group discussion, speaking, anxiety.